DETERMINANTS OF RESIDENTIAL HOUSING CHOICE IN LAGOS STATE, NIGERIA (2011)
The developing world is changing from one of rural villages to that of urban dwellings. The population of Lagos, which stood at 270,000 in 1952/53, rose to 5.69 million in 1991 and was estimated to be 18 million in 2010. This has created excessive demand for housing. Available statistics on housing production showed that between 1974 and 1989, 11422 units of houses were produced. This number fell precipitously to 8162 units between 1994 and 2004. The estimated housing deficit for Lagos in 2010 was 5 million representing 28% of the estimated national housing deficit. The gap between housing delivery and housing demand, engendered by population growth, has necessitated competition and choice making from the available housing alternatives. The literature hardly takes adequate account of the economic and related factors influencing residential housing choice decisions in Third World cities. This study, therefore, investigated the socio-economic determinants of residential housing choice in Lagos, Nigeria. A multinomial logit model, based on the neoclassical consumption framework augmented by hedonic pricing approach, was used to determine the socio-economic determinants of residential housing choice. The specific variables considered were household income, housing price, household size, marital status, ethnicity, gender, and age. The model allowed for the classification of housing units as single-household, multi-household houses, a flat in a block of flats, duplexes, a room in the main building and squatters’ settlements, across high, medium and low density areas. It also has the advantage of comparing the various residential housing choices with the base category (multi-household houses). Cross-sectional data from 4,433 randomly selected rented dwellings across the 20 local government areas in Lagos were used. Diagnostic tests, the variance inflation factor and Box-Cox transformation were used to correct for multicollinearity and functional specification problems. Household income, housing price, household size, marital status and age were the main determinants of the residential housing choice of households. The effects of gender and ethnic variables were not statistically significant. Household income would increase preferences and probabilities for flats, duplexes and single household houses by 7.24, 4.87 and 3.23 times respectively over multi-household houses. The probabilities, however, decreased by 0.02 and 0.85 times for squatters’ settlements and a room in the main building relative to multi-household houses. Households preferences would increase for flats and duplexes by 4.58 and 3.50 times relative to multi-household houses when there is an increase in housing price. The probabilities for squatters’ settlements and a room in the main building are likely to fall by 0.33 and 0.47 times respectively relative to the base category. All these results were statistically significant at the 5.00% level. Other factors such as household size, marital status and age were also statistically significant at the 10.00% level across different residential density areas. Household income and housing price stood out prominently as the major determinants of residential housing choice in Lagos. Economic factors were more important than demographic variables across different residential density areas. Meeting residential needs would require policies aimed at improving incomes and setting appropriate housing prices.